2021
DOI: 10.1002/jnr.24800
|View full text |Cite
|
Sign up to set email alerts
|

Open Practical Laboratories in the Neurosciences: An outreach program for neuroscience communication in middle schools

Abstract: The 1990s were marked as the Decade of the Brain, in response to rapidly increasing interest, by lay audience and scientists alike, on the study of neuroscience (Herculano-Houzel, 2002). From this decade onward, neuroscience gained prominence in the general public; despite this increased interest, however, a decline in the interest of young people in pursuing scientific careers in general and a widespread scientific ignorance in the general populace were observed worldwide in the last 30 years (Gouw et al., 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The age range varied, with 5/23 (21.7%) of the K-12 group articles describing programs for elementary school students, 8/23 (34.8%) describing programs for middle school students, 8/23 (34.8%) describing programs for high school students, and 2/23 (8.7%) describing programs for K-12 students. Only 6/23 (26.1%) of the articles explicitly referenced a historically marginalized demographic, with an even breakdown of elementary ( 11 , 12 ), middle ( 13 , 14 ), and high school groups ( 15 , 16 ). Programs which specifically engaged historically marginalized students are marked with an asterisk (*) in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The age range varied, with 5/23 (21.7%) of the K-12 group articles describing programs for elementary school students, 8/23 (34.8%) describing programs for middle school students, 8/23 (34.8%) describing programs for high school students, and 2/23 (8.7%) describing programs for K-12 students. Only 6/23 (26.1%) of the articles explicitly referenced a historically marginalized demographic, with an even breakdown of elementary ( 11 , 12 ), middle ( 13 , 14 ), and high school groups ( 15 , 16 ). Programs which specifically engaged historically marginalized students are marked with an asterisk (*) in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Only two of the programs included an explicit mention of a long-term mentorship component ( 11 , 28 ), although 7 of the remaining programs facilitated an interaction between K-12 students and a neuroscientist ( 13 , 14 , 16–18 , 29 , 30 ), 3 with a neuroscience undergraduate student ( 12 , 15 , 21 ), 1 with neuroscientists and undergraduates ( 26 ), and 3 with neurology graduate/medical students or resident ( 22–24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous authors have shown that outreach sessions enhance learning and inspire students to consider careers in science (Miranda Feitosa et al, 2021), health and medicine (Hubbard et al, 2005; Zhang et al, 2016) or in higher education more broadly (Saravanapandian et al, 2019). Successful models include half‐day, hands‐on, organ‐based exercises (Clarke et al, 2019) or “Mini Med School” programs (Henderson et al, 2015); “Shadow a Scientist” programs in which students are paired with a scientist mentor for a laboratory visit (Clark et al, 2016); and “Grow up, grow out” programs that return to common themes as students age and develop to increase the complexity of lessons (“grow up”) and the interdisciplinary aspect of lessons as well (“grow out”) (Deal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%